2021
DOI: 10.1111/jre.12948
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of intrabony defects' gingival crevicular fluid

Abstract: Periodontitis is a chronic inflammatory disease attributed to a change in the periodontal microbiota toward dysbiosis, resulting in destruction of the periodontium and eventually tooth loss. 1 As periodontitis progresses, it results in intrabony periodontal osseous defects that are associated with an increased probability of tooth loss. 2 Gingival crevicular fluid (GCF) is both a physiologic fluid and an inflammatory exudate. 3 With the establishment of periodontitis, GCF increases 5.5-fold 4 and becomes enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 44 publications
4
24
3
Order By: Relevance
“…Conversely, the residual lateral walls of infrabony defects may help stabilize the blood clot even in the absence of specific regenerative mediators (Warrer & Karring, 1992). In contrast with previous studies (Koidou et al, 2022; Wikesjö et al, 1994) speculating that intrabony defects offered a unique favourable molecular microenvironment compared with suprabony defects, the present results have shown no difference for the markers included in the present analysis between infrabony and suprabony defects in patients with untreated periodontitis.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Conversely, the residual lateral walls of infrabony defects may help stabilize the blood clot even in the absence of specific regenerative mediators (Warrer & Karring, 1992). In contrast with previous studies (Koidou et al, 2022; Wikesjö et al, 1994) speculating that intrabony defects offered a unique favourable molecular microenvironment compared with suprabony defects, the present results have shown no difference for the markers included in the present analysis between infrabony and suprabony defects in patients with untreated periodontitis.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, our results are in contrast with a previous investigation (Koidou et al, 2022) reporting no significant difference in levels of BMP-2, EGF, SOST and PDGF-AA between infrabony defects and healthy sites. This difference may be ascribed to the smaller sample size adopted in the previous study (Koidou et al, 2022). However, in agreement with the above authors, the present investigation reported no significant difference for RANKL, OPN, PDGF-BB and TIMP-1 between diseased sites and healthy controls.…”
Section: Biomarker Levelscontrasting
confidence: 99%
See 2 more Smart Citations
“…Recently, a work concerning the molecular profiling of intrabony defects was published. Intrabony defects presented significantly increased GCF volume as well as increased IL-1 alpha, IL-1 beta, IL-6, IFN gamma and MMP-8 levels compared to periodontally healthy sites [ 45 ]. The use of local biomarkers offer the possibility for real-time assessment of the healing process.…”
Section: Discussionmentioning
confidence: 99%